2019
DOI: 10.1634/theoncologist.2019-0547
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Variants and Co-Mutations as Genomic Modifiers of Response to Afatinib in HER2-Mutant Lung Adenocarcinoma

Abstract: Background Human epidermal growth factor receptor 2 (HER2)‐mutant lung cancer remains an orphan of specific targeted therapy. The variable responses to anti‐HER2 therapies in these patients prompt us to examine impact of HER2 variants and co‐mutations on responses to anti‐HER2 treatments in lung cancer. Patients and Methods Patients with stage IV/recurrent HER2‐mutant lung cancers identified through next‐generation sequencings were recruited from seven hospitals. The study comprised a cohort A to establish the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 35 publications
5
44
0
Order By: Relevance
“…In a recent study, genotype G778_P780dup and G776delinsVC was found achieving greatest benefit from afatinib (25). In this study, ORR and DCR of afatinib were 15.6% and 68.8%.…”
Section: Specific Mutations and Co-mutations Affect Drug Activitysupporting
confidence: 43%
“…In a recent study, genotype G778_P780dup and G776delinsVC was found achieving greatest benefit from afatinib (25). In this study, ORR and DCR of afatinib were 15.6% and 68.8%.…”
Section: Specific Mutations and Co-mutations Affect Drug Activitysupporting
confidence: 43%
“…Clinical trial results have suggested efficacy of anti-ERBB2 antibody-drug conjugates in lung cancers with ERBB2 mutations (45,46), while TKIs are efficacious in preclinical models of ERBB2-driven NSCLC (23,39), although their performance in the clinic has been variable (47,48). Heterogeneous responses to ERBB2 targeted therapies in lung cancer are thought to be at least partially due to properties unique to specific molecular alterations in ERBB2 (49,50). Our work provides a basis for further studies examining the available suite of ERBB2 targeted therapies and other modalities, such as immunotherapies, to identify effective strategies for cancers driven by ERBB2ΔEx16.…”
Section: Discussionmentioning
confidence: 99%
“…Afatinib, pyrotinib and poziotinib are regarded as HER2‐TKIs. Certain variants, G778_P780dup and G776delinsVC, derive sustained clinical benefits from afatinib, whereas the predominant variant, A772_G775dupYVMA, is resistant to most anti‐ HER2 treatments 12 . In one study, chemotherapy was found to achieve better outcomes than afatinib for YVMA insertions 13 .…”
Section: Discussionmentioning
confidence: 99%